2014
DOI: 10.2147/ijn.s69561
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity and cytotoxicity of multi-walled carbon nanotubes decorated with silver nanoparticles

Abstract: Recently, various nanoscale materials, including silver (Ag) nanoparticles, have been actively studied for their capacity to effectively prevent bacterial growth. A critical challenge is to enhance the antibacterial properties of nanomaterials while maintaining their biocompatibility. The conjugation of multiple nanomaterials with different dimensions, such as spherical nanoparticles and high-aspect-ratio nanotubes, may increase the target-specific antibacterial capacity of the consequent nanostructure while r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“… Sphingomonas spp. Ag-MWCNT (40 or 50 μg/mL) completely inhibited bacterial growth ( Seo et al., 2014 ) Silver and copper nanoparticles MWCNT Medical devices E. coli Ag-MWCNT and Cu-MWCNT exhibited 97% and 89% growth inhibition against E. coli , respectively ( Mohan et al., 2011 ) Copper nanoparticles MWCNT Nonspecified Gram-positive and -negative bacteria; Fungi Cu-MWCNT showed an enhanced inhibitory effect when compared with MWCNT ( Yallappa et al., 2016 ) Titanium oxide-gold (TiO 2 -Au) MWCNT Drug delivery A broad range of Gram-positive and -negative bacteria More than 90% biofilm inhibition was observed in the presence of TiO2-Au-MWCNT ( Karthika et al., 2018 ) Titanium dioxide (TiO 2 ) MWCNT Antimicrobial agents E. coli S. aureus TiO 2 -MWCNT displayed high antimicrobial activity against both bacteria, as demonstrated by the diameter of inhibition zones (≥18 mm) ( Sukkar et al., 2019 ) Cadmium quantum dots (CdS) MWCNT Antimicrobial agents E. coli P. aeruginosa S. aureus The bacteria-killing ability of f-MWCNT-CdS was 87.2% ± 4.1%, 68.9% ± 2.5%, and 46.7% ± 1.4% against E. coli , P. aeruginosa, and S. aureus , respectively ( Neelgund et al., 2012 ) Polymers: Amphiphilic poly(propyleneimine) Dendrimer (APPI) MWCNT Drug delivery Bioimaging Medical devices B. subtilis E. coli S. aureus MWCNTs-APPI hybrid inhibited bacterial growth by 96.6% ± 0.3%, 96.5% ± 0.2%, and 87% ± 0.5% for B. subtilis , S. aureus , and E. coli , respectively ( Murugan and Vimala, 2011 ) O...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Sphingomonas spp. Ag-MWCNT (40 or 50 μg/mL) completely inhibited bacterial growth ( Seo et al., 2014 ) Silver and copper nanoparticles MWCNT Medical devices E. coli Ag-MWCNT and Cu-MWCNT exhibited 97% and 89% growth inhibition against E. coli , respectively ( Mohan et al., 2011 ) Copper nanoparticles MWCNT Nonspecified Gram-positive and -negative bacteria; Fungi Cu-MWCNT showed an enhanced inhibitory effect when compared with MWCNT ( Yallappa et al., 2016 ) Titanium oxide-gold (TiO 2 -Au) MWCNT Drug delivery A broad range of Gram-positive and -negative bacteria More than 90% biofilm inhibition was observed in the presence of TiO2-Au-MWCNT ( Karthika et al., 2018 ) Titanium dioxide (TiO 2 ) MWCNT Antimicrobial agents E. coli S. aureus TiO 2 -MWCNT displayed high antimicrobial activity against both bacteria, as demonstrated by the diameter of inhibition zones (≥18 mm) ( Sukkar et al., 2019 ) Cadmium quantum dots (CdS) MWCNT Antimicrobial agents E. coli P. aeruginosa S. aureus The bacteria-killing ability of f-MWCNT-CdS was 87.2% ± 4.1%, 68.9% ± 2.5%, and 46.7% ± 1.4% against E. coli , P. aeruginosa, and S. aureus , respectively ( Neelgund et al., 2012 ) Polymers: Amphiphilic poly(propyleneimine) Dendrimer (APPI) MWCNT Drug delivery Bioimaging Medical devices B. subtilis E. coli S. aureus MWCNTs-APPI hybrid inhibited bacterial growth by 96.6% ± 0.3%, 96.5% ± 0.2%, and 87% ± 0.5% for B. subtilis , S. aureus , and E. coli , respectively ( Murugan and Vimala, 2011 ) O...…”
Section: Resultsmentioning
confidence: 99%
“…and Sphingomonas spp. after treatment with silver nanoparticle (AgNP)-decorated carboxylated MWCNTs ( Seo et al., 2014 ), the literature reports high inactivation rates of E. coli, B. subtilis, and S. aureus (> 90%) after cell incubation with AgNP-deposited MWCNTs functionalized with an amphiphilic poly(propyleneimine) dendrimer ( Murugan and Vimala, 2011 ). Likewise, more than 90% biofilm inhibition was observed after incubation of Shigella dysenteriae , Proteus vulgaris , K. pneumoniae , Streptococcus pneumoniae , B. subtilis , S. aureus , and C. albicans with titanium oxide-gold ( Karthika et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific metal ions such as silver or zinc ions possess antibacterial properties and can be considered as antibacterial substances. Silver ions are well known to have excellent antimicrobial activity against a wide range of microorganisms 9 , which is why silver-based nanomaterials are being used for its bactericidal activity 10 11 . Interestingly, several studies have shown that silver demonstrates a more potent bactericidal activity against gram-negative bacteria compared to gram-positive bacteria 12 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above-mentioned metallic and polymeric nanoparticles, carbon-based nanostructures have shown antibacterial effects. For instance, the antibacterial activity of fullerene [67] and carbon nanotubes [68,69] ( single-walled or multi-walled) derivatives have been observed. However, the antibacterial mechanism of carbon-based nanostructures is still under debate and has not received particular attention, possibly due to the difficulties of their dispersion in water, especially in case of the carbon nanotubes [70].…”
Section: Nanomaterials As Active Antibacterial Agentsmentioning
confidence: 99%